Atomistic Study of Wet-heat Resistance of Calcium Dipicolinate in the Core of Spores. (15th January 2018) - Mishra, Ankit; Rajak, Pankaj; Tiwari, Subodh; Sheng, Chunyang; Krishnamoorthy, Aravind; Nakano, Aiichiro; Kalia, Rajiv; Vashishta, Priya
ABSTRACT: The extreme heat resistance of dormant bacterial spores strongly depends on the extent of protoplast dehydration and the concentration of dipicolinic acid (DPA) and its associated calcium salts (Ca-DPA) in the spore core. Recent experiments have suggested that this heat resistance depends on the properties of confined water molecules in the hydrated Ca-DPA-rich protoplasm, but atomistic details have not been elucidated. In this study, we used reactive molecular dynamics (RMD) simulations to study the dynamics of water in hydrated DPA and Ca-DPA as a function of temperature. The RMD simulations indicate two distinct solid-liquid and liquid-gel transitions for the spore core. Simulation results reveal monotonically decreasing solid-gel-liquid transition temperatures with increasing hydration. Additional calculations on the specific heat and free energy of water molecules in the spore core further support the higher heat resistance of dehydrated spores. These results provide an insight into the experimental trend of moist-heat resistance of bacterial spores and reconciles previous conflicting experimental findings on the state of water in bacterial spores.